Management of Idiopathic Granulomatous Mastitis Diagnosed by Core Biopsy: A Retrospective Multicenter Study. Issue 4 (12th May 2013) - Oran, Ebru Şen; Gürdal, Sibel Özkan; Yankol, Yücel; Öznur, Meltem; Calay, Zerrin; Tunacı, Mehtap; Soybir, Gürsel Remzi
Abstract Idiopathic granulomatous mastitis (IGM) is a rare, benign, chronic inflammatory condition of the breast, which usually mimics breast carcinoma. The aim of this study was to analyze the clinical features of IGM by identifying a more reliable diagnostic protocol, and evaluating the treatment methods and patient outcomes on follow‐up. We performed a retrospective analysis of 46 patients diagnosed with IGM and managed by the same surgical team between 1999 and 2011, at three high‐volume hospitals. The median age of the patients was 33 years. The most common symptom was painful breast mass (n = 39), followed by abscess (n = 11). All patients underwent ultrasonography (USG). Mammography (MG) and magnetic resonance imaging (MRI) were also performed in 20 patients (43%) and 17 patients (37%), respectively. The mean size of the lesions was 32.8 ± 8.8 mm and ranged from 15 to 50 mm. Preoperative diagnosis of IGM was established by core needle biopsy (CNB) under USG guidance. Eighteen patients (39%) underwent complete excision of the lesion and 25 (54%) were treated with steroids. Three patients treated with steroids subsequently underwent local excision. The mean follow‐up period was 35.4 ± 30.9 months. Eight patients (17%) developed disease recurrence; three of these were successfully treated with steroids, one with surgery, and four with both steroids and surgery. CNB in conjunction with high diagnostic accuracy has a significant role in distinctive diagnosis of IGM and hence, is useful for treatment planning. Treatment can be designated according to the extent and the severity of the disease, and the patient's general health and treatment preferences. Patients with IGM must be closely followed up due to the frequency of disease recurrence.